Desenvolvimento moral e cooperação n'o juízo moral na criança de Piaget - Fontanive, Meriane Carla (2017)
This dissertation is subject to the development of moral judgement and cooperation in the perspective of Jean Piaget. The method of approach is the bibliographical and, for a proper performance of the research, along with the direct focus of the work of Pi aget, especially the moral judgement of the child, recourse to authors who deepen it, such as Yves de La Taille and Lia de Freitas. It is therefore the basis of the work of the moral judgement on the child and the following guiding question: How is the moral judgement of the child and how the concept of cooperation is articulated? In this sense, it proposes to evaluate the possible limits and reach of the notions of duty, justice and cooperation, indicating the reasons for thinking today of moral development with, but beyond Piaget. The work is divided into four chapters. The first, introductory character, situates the problematic, methodology and the Dissertativo route. The second deals with the concepts of duty, awareness of rules and practice of rules, aswell as the stages of development associated with conscience and practice of rules. The third chapter aims to analyze adult coercion and moral realism from the idea of objective accountability and falsehood. In it, it is presented the way it is polite to the will through unilateral respect and the effects of adult coercion, a process that is based on interpersonal relationships. Finally, the fourth chapter addresses the notion of justice, the two morals in the child, cooperation and educational achievement s associated with this latter concept. In this, the study is focused on morality based on mutual respect, which is based on reciprocity between children. It concludes by exploring the role and indicating the scopes of cooperation for the development of moral judgement.